Menu Variety, Price, and Direct Selling in Kedai Jupe Purchases: Keragaman Menu, Harga, dan Penjualan Langsung dalam Pembelian di Kedai Jupe - Amalia, Syifani Nur; Farida , Siti Ning (Academia Open, 2026)
General Background Culinary business competition requires marketing strategies that address consumer behavior, product communication, pricing, and food option diversity. Specific Background Kedai Jupe operates in the spicy food segment and applies direct selling, competitive pricing, and varied menus to attract consumers. Knowledge Gap Although prior studies have examined similar marketing variables, limited research has focused on Kedai Jupe and the role of direct selling as a primary strategy in this specific consumer context. Aims This quantitative study analyzes the relationship between direct selling, price, and menu variety with consumer purchase decisions using 156 purposively selected respondents and multiple linear regression. Results The findings show that the three variables jointly had a positive and significant relationship with purchase decisions, with F = 84.316 and p < 0.001. Partially, direct selling was significant with t = 4.676 and p < 0.001, price was significant with t = 2.041 and p = 0.043, and menu variety was significant with t = 5.042 and p < 0.001. The model explained 62.4% of the variance in purchase decisions. Novelty The study provides context-specific evidence on how direct selling, pricing, and menu diversity operate together in a local culinary business. Implications The findings suggest that integrated marketing strategies combining interpersonal sales communication, appropriate pricing, and diverse food options can support consumer decision-making in culinary enterprises. Highlights: Three predictors were statistically significant both jointly and individually. Regression explained 62.4% of consumer choice variance. The largest coefficient appeared in the product option variable. Keywords : Direct Selling, Menu Options, Price, Purchase Decision